Scrutiny on the grammatical error of descriptive text written by the first semester public health students Universitas Faletehan - Kety Soraya (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
In English Competency the students should master four skills namely speaking, reading, writing and listening. On the other hand most of students found many barriers to achieve this competency, particularly in writing due to writing is not simple but writing is long process. This study is intended to analyze, find out the types of errors, and the factors for grammatical error in students composition. The use of articles, verbs, adjectives, adverbs, nouns, preposition, and conjunctions are the focus of the analysis. The errors are analyzed through the procedure of identification, description, categorization, classification, calculation and interpretation. The errors were then classified into four types namely omission, addition, misformation, and misordering then they were counted and interpreted. Altogether they were 1401errors in student’s descriptive text. They covered 495 (35.33%) errors of articles, 280 (19.98%) errors of nouns, 225 (16.05%) errors of preposition, 116 (8.27%) errors of adjectives, 62 (5.42%) errors of verb, 58 (5.07%) errors of conjunction, 44 (3.84%) errors of pronouns, and 110 (7.85%) errors of verbs. Based on the type of errors omission errors got the highest frequency. It happened 475 (33.9%) followed by misformation and misordering, addition errors 190 (13.56%). There were various frequencies of errors found from each type. Omission errors included 200 (35.33%) from 495 errors of articles, Nouns 90 (19.98%) from 280 error of nouns, preposition 70 (16.05%) from 225 errors of prepositions, conjunction 40 (4.99%) from 70 errors of conjunction, pronoun 30 (4.63%) from 65 of pronouns, verb 40 (7.85%) from 40 errors of verbs, adjective 30 (8.27%) from 30 errors of adjectives. Addition errors 50 ( 16.05.33%) from 225 errors of preposition, nouns 35 (19.98 %) from 280 errors of nouns and adjective 30 (2.85%) from 30 adjectives. The misordering errors of articles are clearly seen that they got the highest frequency among others. It took place 200 times (35.33%) from 495 of articles. Great tendency to omit and misform, article, nouns, and preposition is influenced by the skill habit of L1, as well as misordering errors of articles, preposition, nouns, and adjective. It is interpreted hat differences of the structure of L1 and L2 greattly influence the learners to make grammatical errors in writing English composition. Another factor that the causes the errors in incomplete of the target language itself.